THE EFFECT OF PROVIDING TAX INCENTIVES AMID THE COVID 19 PANDEMIC ON THE LEVEL OF COMPLIANCE OF SME TAXPAYERS IN SUBANG DISTRICT - Uswatun Hasanah (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2022)
The Covid-19 pandemic, which originated in Wuhan China, is still a hot issue that continues to be discussed since the emergence of late 2019. The Covid-19 virus has entered Indonesia and the government has set a covid response situation starting from 2 March 2020. Various policies have been issued by the government to prevent the spread of the covid-19 virus on a large scale, one way is to limit the activities of local residents such as large-scale restrictions (PSBB) in certain areas, of course this affects the economy in several countries and regions including Indonesia. As a result of this pandemic, the people's economy has weakened and the government finally issued a